Strategi Advertising Bisnis Online OLX - Putu Denny Prathama Ayub (Universitas Pendidikan Nasional, 2016)
This study aims to analyze and to interpret consumer’s perception towardadvertisement of Olx.com through television. The method has been applied for this study wasqualitative descriptive approach with triangulation and in-depth interview to problem solvingby conduct comprehending and collet data in-whole and intact from research object in orderto get focus overview from observation result and observation from site.Conclusion of this study is the consumer’s perception toward advertisement ofOlx.com through television media is positive match with message send from theadvertisement. All of this written in expression from some informant who declare thatperception is near same but in different expression that is Olx.com easy to use and free.Keyword : Advertising, and Consumer Behavior.